The Prevalence of Mental Disorders among Serving Soldier Requiring Admission - Rawal, Namrata; Thapa, Praswas; Bista, Yadav (Medical Journal of Shree Birendra Hospital, 2013)
Introduction: Numerous studies have been done to study the psychiatric conditions in army personnel but none have been done in Nepalese army personnel. The purpose of the present study was to determine the prevalence of common mental disorders among Nepalese Army Personnel who were admitted in psychiatric ward. Methods: Retrospectively 186 case records of Nepalese Army Personnel, who received treatment at the inpatient psychiatric ward over a period of one year (15th May 2010 to 15th May 2011) , were included in this study. Descriptive analysis of their demographic data and types of psychiatric disorders was done using SPSS v16. Results: Among the 186 patients who were admitted during the study period, 184 (98.92 %) were male. The most common age range was 21-30 years (70.43%). The prevalence of the first ten rank of mental disorders among Nepalese Army Personnel were Major Depression (25.27%), Alcohol dependence (22.58%), Schizophrenia (14.67%), Bipolar disorder (8.6%), Anxiety disorder(6.52%), Substance induced psychotic disorder(4.35%), Schizoaffective disorder(3.26%), Deliberate self harm (2.72%), Malingering(2.72%) and Poly substance dependence (2.72). Conclusions: The most common prevalence of mental disorders among inpatient of Nepalese Army Personnel in psychiatric department in the year 2010-11 were Major depressive disorder, Alcohol dependence and Schizophrenia. Medical Journal of Shree Birendra Hospital; July-December 2012/vol.11/Issue2/14-17 DOI: http://dx.doi.org/10.3126/mjsbh.v11i2.7902